EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN PETA KONSEP PADA MATERI PERSAMAAN KUADRAT DITINJAU DARI SIKAP ILMIAH PESERTA DIDIK KELAS X SMA DI KABUPATEN KUDUS TAHUN PELAJARAN 2013/2014 - Handayani, Endang Sri; Mardiyana, Mardiyana; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purpose of this study was to determine the effect of cooperative learning model Jigsaw with the concept map, cooperative learning model Jigsaw without a concept map, and the direct instruction model with a review of the scientific attitude of students towards learning achievement. This type of research was a quasi-experimental research with 3x3 factorial designs. This research was implemented in the month of September 2013 to November 2013. The X grade students of Senior High School in Kudus Regency with 2013/2014 academic year was the population of this research. The instrument used to collect the data were UAN, scientific attitude questionnaire, and mathematics achievement tests with the topic of quadratic equation in the form of multiple choice. Test requirements include test data analysis used Lilliefors test for normality and homogeneity test used the Bartlett test. Analysis of the data used two-way variance with unbalanced cells. The conclusion of this study were: (1) cooperative learning model Jigsaw with the concept map has better mathematics learning achievement than the cooperative learning model Jigsaw without a concept map and the direct instruction model, the cooperative learning model Jigsaw without a concept map has mathematics learning achievement as good as the direct instruction model; (2) the high scientific attitude students have better mathematics learning achievement than the medium and lowÂ scientific attitude students, the medium scientific attitude student have mathematics learning achievement as good as the low scientific attitude students; (3) there is no interaction between learning model to the level of scientific attitude of students towards mathematics learning achievement; (4) there is no difference between the learning achievement of students in each level of the scientific attitude for each learning model.Keywords: cooperative learning model , Jigsaw , concept maps , scientific attitude